Multi‐polarised SAR imaging simulation of ship on heavy sea. Issue 20 (28th August 2019) - Chen, Yanxi; Guo, Kunyi; Wu, Biyi; Sheng, Xinqing
Abstract : Multi‐polarisation synthetic aperture radar (SAR) imaging simulation of ship under heavy sea condition is presented here. Full‐wave method is used to compute the fully polarimetric backscattered waves of the complex scene of ship and sea surface. The influence by heavy sea on SAR imaging results is investigated; furthermore, the suppression effects to sea waves by different polarisations are evaluated in detail.